Desain Pembelajaran Model Dack and Carey Terhadap Pemahaman Konsep Matematika Pada Materi Menyederhanakan Bentuk Aljabar - Rosa Yuliana; Lukman El Hakim; Tian Abdul Aziz; Flavia Aurelia Hidayat (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This article examines the development of mathematics learning design using the Dick and Carey model in material simplifying algebra forms for class VII SMPN 217 Jakarta. Learning design refers to the process of planning and developing effective learning structures, strategies and activities to achieve desired learning goals. The purpose of writing this article is to explain the steps for developing learning design by applying the Dick and Carey model in designing mathematics learning on material that simplifies algebraic forms. The results of developing designs using the Dick and Carey model in developing mathematics learning designs can help teachers in designing and implementing learning.